Pseudo-problems : how analytic philosophy gets done - Sorensen, Roy A. (Routledge, 1993)
A fast-moving, fascinating alternative history of twentieth century analytic philosophy. Using many examples, Sorenson explains how problems are dissolved rather than solved. This is a fine example of what philosophical analysis should be.